IMPROVING MODIFIED ICOLD METHOD WITH LOSS OF LIFE INDEX FOR DAM SAFETY RISK ASSESSMENT - Henrianto, A.; Triweko , R. W.; Yudianto, D. (Journal of Civil Engineering, Science and Technology, 2020)
This research paper explains the results of the prediction analysis of the number of lives lost in the event of a catastrophic dam collapse in Indonesia as a further consideration in assessing the level of risk of dam safety. The proposed procedure is to make a new prediction index of the number of lives lost (LoL) as the development of a risk index of evacuation requirements from Risk Affected Populations (PENRIS), on the Modified ICOLD Method which is always used in Indonesia. This study, resulting in a regression equation as a correlation between PENRIS and LoL, takes its source from various catastrophic dam collapse events that have occurred in the world including Indonesia. Furthermore the regression equation is integrated with the standard determination of the level of risk of dam safety used in Indonesia and the world, for conditions with and without a disaster early warning system based on the Graham formula (2010). Further analysis of the Emergency Action Plan (EAP or RTD) of 16 dams in Indonesia as a sample, gives an indication that the implementation of an early warning system will reduce the amount of LoL by almost 100% if implemented according to design. This research, with its focus on developing a prediction index for the number of LoL, proves that in Indonesia, where there are still many dams even though they already have RTDs, and have not conducted a disaster-based space arrangement based on predicted LoL numbers, the reduction in the value of dam security risks can only be optimal in the range of 50 % of the total dam studied.